Investigating the impact of climate change on irrigation and crop water requirements of Bhadra and Tungabhadra command area: A CMIP-6 GCMs and CROPWAT 8.0 approach - G. K. Rudraswamy; N. V. Umamahesh (Water Supply, 2024)
The effect of climate change on water availability and agriculture water demand is crucial for assessing agricultural productivity and economic development in semi-arid regions. The present study examines the crop water requirement (CWR) and irrigation water requirement (IWR) of the Bhadra and Tungabhadra (TB) command areas, with a focus on forecasting future irrigation water needs. Using the CROPWAT 8.0 software, CWR and IWR were estimated for the base period (1975–2010) and three future periods: near future (2023–2048), middle future (2049–2074), and far future (2075–2099). Five best-performing Global Climate Models (GCMs) were utilized under two shared socioeconomic pathways (SSPs) (i.e., SSP-245 and SSP-585). The results indicate that in the Bhadra command area, CWR increases during the kharif season under both SSPs. However, monthly IWR for the kharif season experiences a significant decrease, except for June. In the TB command area, CWR shows a decreasing trend, while monthly IWR increases for both seasons in future periods. The SSP-585 scenario exhibits a more pronounced increment in CWR and IWR for both command areas. The results enhance comprehension of water demand dynamics in agricultural areas, assisting policymakers and stakeholders in devising effective strategies to address climate change impacts on agriculture and encourage sustainable practices. HIGHLIGHTS Future crop water and Irrigation water requirements are evaluated for Bhadra and Tungabhadra command areas.; Compromise programming for selection of best performing GCMs and CROPWAT 8.0 for modeling variation in future CWR and IWR under changing climate for SSP-245 and SSP-585 scenarios.; The study enhances understanding water demand dynamics in command areas, assisting policymakers and stakeholders in developing strategies to address climate change impact and promote sustainable practices.;